In vivo imaging of bone collagen dynamics in zebrafish - Hiromu Hino; Shigeru Kondo; Junpei Kuroda (Bone Reports, 2024)
Type I collagen plays a pivotal role in shaping bone morphology and determining its physical properties by serving as a template for ossification. Nevertheless, the mechanisms underlying bone collagen formation, particularly the principles governing its orientation, remain unknown owing to the lack of a method that enables continuous in vivo observations. To address this challenge, we constructed a method to visualize bone collagen by tagging with green fluorescent protein (GFP) in zebrafish and observed the interactions between osteoblasts and collagen fibers during bone formation in vivo. When collagen type I alpha 2 chain (Col1a2)-GFP was expressed under the control of the osteoblast-specific promoters osx or osc in zebrafish, bone collagen was observed clearly enough to identify its localization, whereas collagen from other organs was not. Therefore, we determined that this method was of sufficient quality for the detailed in vivo observation of bone collagen. Next, bone collagen in the scales, fin rays, and opercular bones of zebrafish was observed in detail, when bone formation is more active. High-magnification imaging showed that Col1a2-GFP can visualize collagen sufficiently to analyze the collagen fiber orientation and microstructure of bones.Furthermore, by simultaneously observation of bone collagen and osteoblasts, we successfully observed dynamic changes in the morphology and position of osteoblasts from the early stages of bone formation. It was also found that the localization pattern and orientation of bone collagen significantly differed depending on the choice of the expression promoter. Both promoters (osx and osc) used in this study are osteoblast-specific, but their Col1a2-GFP localizing regions within the bone were exclusive, with osx region localizing mainly to the outer edge of the bone and osc region localizing to the central area of the bone. This suggests the existence of distinct osteoblast subpopulations with different gene expression profiles, each of which may play a unique role in osteogenesis.These findings would contribute to a better understanding of the mechanisms governing bone collagen formation by osteoblasts.